2013
DOI: 10.1016/j.neuron.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Using Whole-Exome Sequencing to Identify Inherited Causes of Autism

Abstract: Summary Despite significant heritability of autism spectrum disorders (ASDs), their extreme genetic heterogeneity has proven challenging for gene discovery. Studies of primarily simplex families have implicated de novo copy number changes and point mutations, but are not optimally designed to identify inherited risk alleles. We apply whole exome sequencing (WES) to ASD families enriched for inherited causes due to consanguinity and find familial ASD associated with biallelic mutations in disease genes (AMT, PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
347
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(366 citation statements)
references
References 74 publications
12
347
0
7
Order By: Relevance
“…The 3 high-morbidity subgroups had distinct pathophysiologies; the heterogeneity of the ASD comorbidity spectrum mirrors the heterogeneity observed in genome-wide studies of variants associated with ASD [65][66][67] and gene expression. 68 How our pathophysiological subgroups map to genome-scale heterogeneity remains unknown, but our subgroups suggest a group structure worth investigating with these molecular measures.…”
Section: Figurementioning
confidence: 74%
“…The 3 high-morbidity subgroups had distinct pathophysiologies; the heterogeneity of the ASD comorbidity spectrum mirrors the heterogeneity observed in genome-wide studies of variants associated with ASD [65][66][67] and gene expression. 68 How our pathophysiological subgroups map to genome-scale heterogeneity remains unknown, but our subgroups suggest a group structure worth investigating with these molecular measures.…”
Section: Figurementioning
confidence: 74%
“…102 However, recent data using exome and whole genome sequencing methods suggest the yield of such testing for clinically informative variants may be much higher. 103,104 Moreover, although the contribution of specific biomarkers to risk prediction may be modest, combined results from a panel of predisposing biomarkers can produce information about an individual' s probability of developing ASD. 105 Consideration of several biomarkers at once is consistent with the multitude of genetic and epigenetic factors (and potentially other biological factors [eg, immune, indices of atypical brain growth/connectivity]) that likely play a role in vulnerability to ASD in many children.…”
Section: Examine the Effectiveness Of Repeat Screeningmentioning
confidence: 99%
“…This project identified an enrichment of implicated loci with genes that were regulated by neuronal activity [6]. These studies also identified a number of mutations in these pedigrees, for example the endosomal Na + /H + exchanger 9 (NHE9), glycine metabolic genes, and SYNE1 [6,181]. Some of the genes implicated showed comparable mutations in autism pedigrees without recent shared ancestry.…”
Section: Recessive Loci In Asdmentioning
confidence: 93%
“…Some of the genes implicated showed comparable mutations in autism pedigrees without recent shared ancestry. In addition, some pathways showed evidence supportive of transheterozygous mutations, that is, heterozygous mutations in 2 genes in a common pathway [181]. This genetic mechanism is commonly encountered in model organisms [182]; however, this mechanism of inheritance has not been exhaustively studied.…”
Section: Recessive Loci In Asdmentioning
confidence: 99%